Pelaksanaan Desentralisasi dan Good Governance Kabupaten Malang di Desa Ngadas - Dilla Maulida; Hana Sausan; Salwa Nazhira; Firman Manan (Epistemik: Indonesian Journal of Social and Political Science, 2023)
Decentralization is a policy that develops in democratic countries. Indonesia is one of the democratic countries that has issued a policy of regional autonomy which then also influences the governance process in the smallest scope, namely village administration. Ngadas Village is a village located in Poncokusumo District, Malang Regency, Central Java. This research focuses on the implementation of regional autonomy, community participation and the formulation of village regulations to achieve good governance. This study used a qualitative method with the data collection process by observation, interviews and documentation. The results of the study show that the people of Ngadas Village place more emphasis on customs and still believe in traditional shamans, the role of traditional shamans is very clearly visible in politics in the inauguration of the position of village head as well as traditional head. The participation of the Ngadas community is included in the category of active participation, the community receives invitations or information regarding deliberations through the RT who come directly to residents' homes. Ngadas Village was able to achieve good governance in a way that was different Compared to other villages, the uniqueness of the village of Ngadas makes politics healthier by emphasizing customary law.